First Year Occupational Therapy Students’ Clinical Reasoning Approach to Addressing Challenging Behaviors Related to Sensory Processing Using a Simulated Case Study - Bryan M. Gee; Kelly E. Thompson; Jane Strickland; Lucy Jane Miller (Journal of Occupational Therapy Education, 2017)
Occupational therapy students must be prepared to use clinical reasoning to select appropriate interventions for children with sensory processing disorders (SPDs). Although these interventions are typically taught in entry-level occupational therapy programs, there is little information regarding the method by which occupational therapy students are taught a clinical reasoning process to determine which sensory processing intervention to use with pediatric clients. A problem-solving framework called A SECRET was used to teach students clinical reasoning for children with SPDs, via an online, module-based course. Following the module, the students were tested with an online assessment tool regarding their ability to discriminate between appropriate and inappropriate intervention strategies, and to articulate their rationale to demonstrate how they clinically reasoned through a complex client case. Eight students participated in a focus group to provide their perceptions of the online delivery of the content and the A SECRET reasoning process. Five descriptive representations emerged from the qualitative data analysis: the A SECRET Process, Self-Regulation, the Occupational Therapy Practice Framework, Participation, and Safety/Security. The findings suggest an inherent value for online learning to assist occupational therapy students in their program’s first year to learn the A SECRET process and then clinically reason through a simulated case study.